Objective measurement of sedentary time and physical activity in people with rheumatoid arthritis: protocol for an accelerometer and activPAL(TM) validation study - O’Brien, Ciara M. (Mediterr J Rheumatol, 2019)
BACKGROUND: The accurate measurement of sedentary time and physical activity in Rheumatoid Arthritis (RA) is critical to identify important health consequences and determinants of these behaviours in this patient group. However, objective methods have not been well-validated for measurement of sedentary time and physical activity in RA. AIMS: Specific objectives are to: 1) validate the ActiGraph GT3X+ accelerometer and activPAL3(μTM) against indirect calorimetry and direct observation respectively, and define RA-specific accelerometer cut-points, for measurement of sedentary time and physical activity in RA; 2) validate the RA-specific sedentary time accelerometer cut-points against the activPAL3(μTM); 3) compare sedentary time and physical activity estimates in RA, using RA-specific vs. widely-used non-RA accelerometer cut-points. METHODS: Objective 1: People with RA will wear an ActiGraph GT3X+, activPAL3(μTM), heart rate monitor and indirect calorimeter, whilst being video-recorded undertaking 11 activities representative of sedentary behaviour, and light and moderate intensity physical activity. Objectives 2 and 3: People with RA will wear an ActiGraph GT3X+ and activPAL3(μTM) for 7 days to measure free-living sedentary time and physical activity. DISCUSSION: This will be the first study to define RA-specific accelerometer cut-points, and represents the first validation of the ActiGraph accelerometer and activPAL(TM), for measurement of sedentary time and physical activity in RA. Findings will inform future RA studies employing these devices, ensuring more valid assessment of sedentary time and physical activity in this patient group.